Value assumptions of the teachers in classroom-based English language assessment practices of two private schools in Laguna, Philippines - GONZALES, HOLYANNE KAE (Archīum Ateneo, 2019)
This study uncovers the features (characteristics) of classroom-based English language assessment practices of two private schools in Laguna, Philippines. In particular, it describes how the classroom-based English language assessment practices are carried out and reveals what value assumptions are embedded in these assessment practices. The study adapted Messick's (1989) value implications in his validity matrix, and Bernstein's pedagogic device (Motteram, 2016) to examine the assessment practices of six English language teachers from the two institutions. Data were gathered from classroom observation, collection of testing materials, and audio-taped interviews with the English language teachers. The results reveal that in the assessment practices the monolingual paradigm persists. However, English language teachers have shown that by considering the needs of the learners, the monolingual paradigm can be challenged through alternative approaches in language assessment.